Development of UNO Game Media in Mathematics Learning Integer Operations - Jumaroh, Juju; Surachman, Shintia Permata; yaroh, Yaroh (Etunas Sukses Sistem, 2022)
This research is a development research that aims to improve the UNO game media using the ADDIE model (Analysis, Design, Development of Production, Implementation or Delivery, Evaluations) to be used in mathematics education media for the Integer Operations module. This research was tested on class by selecting 15 students to be exact who had taken the integer operations learning module. This study uses the test method, which is to provide questionnaires to students, as well as documentation. The instruments used in this study were the module aspect feasibility validation sheet, media feasibility validation, practicality and student comment sheets. The results of the analysis from the validator and student comments show that the UNO card can help sharpen students' brains in counting activities because they can learn by playing without feeling bored. The use of UNO card media has a positive impact on improving student learning outcomes. This can ensure that the UNO card game can attract attention and can make it easier for students to learn mathematics.